STATE’S AUTHORITY RIGHTS OVER LAND IN INDONESIA - Awaluddin, Awaluddin (Tadulako University, 2017)
The basic principle mentioned about the right over land by state is very basic according Article 33 Paragraph (3) of the 1945 Constitution which states